Гіркокаштан звичайний (Aesculus hippocastanum L.) у зелених насадженнях Києва: проблеми та перспективи культури у сучасних умовах - Levon, F.M.; Shumik, M.I.; Ilyenko, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The uptodate assessment of green plantings, and Aesculus hippocastanum L. is reconciled, in particular, in Kyiv. It is certified, that on the general status the yielded plantations respond the norm, and only on the separate arterial highways overstrained with a carrier a certain unit of trees A. hippocastanum demands accepting of emergency measures on enriching of their status. Necessity of realisation for immediate prospects of openings on changing of weakened trees in connection with their ageing and magnification of a technogenic press on an urban environment is reasonable. It is reasonable relevance from urban authorities of accepting of the general measures on care of street plantations and their protection, initiatings in scales of a city of realisation of monitoring of green plantings and soils, ecological monitoring etc.